Latin America : New Challenges to Growth and Stability - Iakova, Dora (International Monetary Fund, 2014)
Over the past fifteen years countries in Latin America made tremendous progress in strengthening their economies and improving living standards. Although output fell temporarily during the global financial crisis, most economies staged a rapid recovery. However, economic activity across the region has been cooling off and the region is facing a more challenging period ahead. This book argues that Latin America can rise to the challenge, and policymakers in the region are already implementing reforms in education, energy, and other sectors. More is needed, and more is possible, in Latin America's quest to continue to improve living standards.